Therapeutic properties of stingless bee honey in comparison with European bee honey - Amin, Fatin Aina Zulkhairi; Sabri, Suriana; Mohammad, Salma Malihah; Ismail, Maznah; Chan, Kim Wei; Ismail, Norsharina; Mohd Esa, Norhaizan; Zawawi, Norhasnida (Hindawi, 2018)
Both honeybees (Apis spp.) and stingless bees (Trigona spp.) produce honeys with high nutritional and therapeutics value. Until recently, the information regarding potential health benefits of stingless bee honey (SBH) in medical databases is still scarce as compared to the common European bee honey (EBH) which is well known for their properties as therapeutic agents. Although there have been very few reports on SBH, empirically these products would have similar therapeutic quality as the EBH. In addition, due to the structure of the nest, few studies reported that the antimicrobial activity of SBH is a little bit stronger than EBH. Therefore, the composition of both the types of honey as well as the traditional uses and clinical applications were compared. The results of various studies on EBH and SBH from tissue culture research to randomised control clinical trials were collated in this review. Interestingly, there are many therapeutic properties that are unique to SBH. Therefore, SBH has a great potential to be developed for modern medicinal uses.